2016
DOI: 10.1021/acsmedchemlett.5b00495
|View full text |Cite
|
Sign up to set email alerts
|

Triazolylthioacetamide: A Valid Scaffold for the Development of New Delhi Metallo-β-Lactmase-1 (NDM-1) Inhibitors

Abstract: ABSTRACT:The metallo-β-lactamases (MβLs) cleave the β-lactam ring of β-lactam antibiotics, conferring resistance against these drugs to bacteria. Twenty-four triazolylthioacetamides were prepared and evaluated as inhibitors of representatives of the three subclasses of MβLs. All these compounds exhibited specific inhibitory activity against NDM-1 with an IC 50 value range of 0.15−1.90 μM, but no activity against CcrA, ImiS, and L1 at inhibitor concentrations of up to 10 μM. Compounds 4d and 6c are partially mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 35 publications
(56 reference statements)
2
38
0
Order By: Relevance
“…A possible reason for this is that the kind and position of the substituents in the benzene ring greatly affected the affinity between the inhibitor molecule and MβLs. In line with our previous research [14][15][16][17], electron-absorbing groups have a greater ability to improve the affinity of inhibitors and MβLs. The nitro group has been proven to be an effective zinc ligand in the complex of carboxypeptidase A/aromatic nitropropionic acid [18].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A possible reason for this is that the kind and position of the substituents in the benzene ring greatly affected the affinity between the inhibitor molecule and MβLs. In line with our previous research [14][15][16][17], electron-absorbing groups have a greater ability to improve the affinity of inhibitors and MβLs. The nitro group has been proven to be an effective zinc ligand in the complex of carboxypeptidase A/aromatic nitropropionic acid [18].…”
Section: Discussionsupporting
confidence: 86%
“…Antibiotics 2020, 9, 99 2 of 7 design of MβL inhibitors because the sulfur atom can reduce the MβLs activity by binding to the zinc ions which are enzyme active center and replacing the bridging water molecules [12,13]. Recently, our group has reported that thioacetamide derivatives exhibit biological activity which may inhibit MβLs [14][15][16][17]. In addition, some of the thioacetamides showed broad-spectrum inhibitory activity against all three subclasses of MβLs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow‐up study, the team reported a new series of NDM‐1 inhibitors based on triazolylthioacetamide scaffolds. These compounds all showed specific inhibitory activity against NDM‐1 with IC 50 values ranging from 0.15 to 1.90 μM (Xiang et al., ; Zhai et al., ). At the same time, the inhibitory effect of the azolylthioacetamide compound on VIM‐2 was also discovered.…”
Section: Progress In Designing Metallo‐β‐lactamase Inhibitorsmentioning
confidence: 99%
“…Recently, we found that azolylthioacetamides are the potent MβL inhibitors [23][24][25][26], these compounds showed broad-spectrum inhibition on CcrA [24], NDM-1 [23,24,26], ImiS [24][25][26], and L1 [24], as the representative of three subclasses enzymes, respectively. Further, we reported an aromatic carboxyl substituted azolylthioacetamide as an inhibitor of VIM-2, which provided the binding via the complex crystal structure of enzyme and inhibitor [27].…”
Section: Introductionmentioning
confidence: 99%